Pendeteksi Jenis Autis pada Anak Usia Dini Menggunakan Metode Linear Discriminant Analysis (LDA) - Edwar Budiman; Edy Santoso; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Every human that live into the world is surely will pass several phase into their life's, like growth phase, development phase, etc. Several change in physical appereance in child called growth, and development is obtained through process of social and psychological. There's a time in child phase called golden age, it's where the most critical time of growth and development in child, must be put to a good use because golden age will never come back. In time when child reach the golden age, to prevent anything harm to the child, as a parent must know all the things that affect the child. One of the things that can be experienced by the child is autism. Autism is mental condition that characterized by having difficulty in social life and some of them is having trouble with physical too. In Indonesia, 1 from 590 child is diagnosed by autism, and this number is increasing in each year. So to prevent this, early intervention to autism is needed to make child have the right treatment and to decreasing the symptomps of autism. There are three types of autism, slight autism, regular autism, severe autism according to condition of the people that having autism. Classification that can help to identify autism is linear discriminant analysis (LDA) method. LDA method also have good accuracy to identify autism. With 75 data, system with LDA method can identify autism with 88% accuracy